Unlocking the Mathematical Mind: A Comparative Insight into Undergraduate and Graduate Student Literacy - Peni, Nur; Pratiwi, Septia; Prabowo, Anggita; Alam, Sri Rahayu; Rahmawati, Dewi; Lua, Muhammad Febriyan; Setiawan, Aldo (Graduate School of Universitas Negeri Malang, 2024)
The study explores the nuances of students' knowledge, self-assurance, and difficulties when navigating the domains of numeracy and logical-mathematical reasoning by evaluating and comparing the levels of mathematical literacy, numeracy, and logical-mathematical thinking among higher-education students. This research uses a thorough survey covering various mathematical literacy dimensions, such as the capacity to apply mathematical ideas in practical contexts, comprehension of numeracy and literacy, assurance when working with numerical data, and the influence of emotional variables on rational thought. Our analysis, based on replies from graduate and undergraduate students at renowned Indonesian universities, shows that self-assessed competency is generally moderate to good, with significant differences between academic subjects and study levels. The research indicates a potential relationship between curriculum focus and mathematical literacy since some students from specific programs have a marginally more significant skill level. The results highlight how crucial it is to incorporate real-world applications and emotional intelligence into mathematical education to improve student confidence, comprehension, and engagement. This study offers important insights into the state of mathematical literacy today. It suggests possible areas for curriculum development and pedagogical innovation to better prepare our future professionals for the demands of a digital and data-driven world as we map out the future of educational strategies in higher education.